Faktor-Faktor yang Mempengruhi Pengelolaan Keuangan Desa pada Desa Marisa Selatan Kecamatan Marisa Kabupaten Pohuwato - Muhammad Anas (Pusat Riset dan Inovasi Nasional, 2024)
In managing village finances, reliable human resources, accountability and transparency are needed because considering that the funds disbursed by the central government are very large in amount for each village, reaching hundreds of millions of rupiah and if they are not managed well, there are concerns about the development that was originally planned and deliberation at the village level will fail miserably. This research was conducted using the saturated sample method, resulting in 59 respondents who knew village financial management. This research uses multiple linear regression analysis methods. Where the results of the research show that Human Resources (X1) partially have a significant influence on village financial management (Y) with a tcount value of 2.12 > ttable of 2.00 with a significance value of 0.03 < 0.05, accountability (X2) partially has a significant influence on village financial management (Y) tcount value of 2.16 > ttable of 2.00 with a significance value of 0.02 < 0.05. transparency (X3) partially has a significant influence on village financial management (Y) tcount value of 2.34 > ttable of 2.00 with a significance value of 0.02 <0.05 and simultaneously the human resources variable (X1) , accountability (X2) and transparency (X3) have a significant influence on village financial management (Y) amounting to 20.78 > 5.68 with a significance value of 0.04 < 0.05.